The European influence on workers' compensation reform in the United States - LaDou Joseph (BMC, 2011)
Abstract Workers' compensation law in the United States is derived from European models of social insurance introduced in Germany and in England. These two concepts of workers' compensation are found today in the federal and state workers' compensation programs in the United States. All reform proposals in the United States are influenced by the European experience with workers' compensation. In 2006, a reform proposal termed the Public Health Model was made that would abolish the workers' compensation system, and in its place adopt a national disability insurance system for all injuries and illnesses. In the public health model, health and safety professionals would work primarily in public health agencies. The public health model eliminates the physician from any role other than that of privately consulting with the patient and offering advice solely to the patient. The Public Health Model is strongly influenced by the European success with physician consultation with industry and labor.